Smart sensors for industry 4.0 fundamentals, fabrication and IIoT applications - Mishra, Brojo Kishore 1979-; Mallik, Sandipan; Le Dac-Nhuong 1983- (Scrivener Publishing, 2024)
Prepare to delve into the realm of Industry 4.0. Smart Sensors of Industry 4.0: Fundamentals, Fabrications is a comprehensive compilation that merges the latest research in the fabrication of Industry 4.0. Having endorsed advanced methods in the smart industry, this book serves as a guide to enlighten readers on the pivotal role of sensors. These sensors form versatile systems, enhancing efficiency and elevating the customer experience in the current commercial environment.Navigate through the pages that detail IoT system integration and lloT applications to promote a vision for the realization of the smart industry. For a more profound understanding of how sensors execute computation-based measurements, explore compelling insights for IoT sensors across various industrial applications. With IoT developments, advanced sensors are developing, resulting a necessity for IoT sensors to be used for several industrial applications
Keywords: Elektronik, Elektrotechnik, Nachrichtentechnik